Proceedings of the Proceeding of the 2nd International Conference Education Culture and Technology, ICONECT 2019, 20-21 August 2019
DOI: 10.4108/eai.20-8-2019.2288123
|View full text |Cite
|
Sign up to set email alerts
|

The Strategic Orientation of Entrepreneurship on The Small and Medium Business At Batik Kudus As A Heritage Culture

Abstract: Kudus is a small town with a variety of diversity found in the community. In the city of Kudus there are also 2 Sunan namely "Sunan Muria" and "Sunan Kudus". Sunan Kudus himself left a teaching "Gusjigang", which is an acronym for "bagus, ngaji, dagang". This philosophy motivates Kudus residents in trading and entrepreneurship, in Kudus the trade and SME sectors are the economic drivers and one of the backbone of the economy of Kudus Regency, including Kudus Batik. The Kudus Batik Industry is an industry that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to several studies, virtual tours have not been found through digital showrooms for creative industry products that also allow for interaction between creative industry players and consumers. If this is successful, it will positively impact the development of Indonesia's creative industries (Rizkiyanti et al, 2021;Wahyudi et al, 2021;Zahro et al, 2019). Therefore, this service has been carried out in a virtual tourism-based digital batik village as a platform to promote batik in Bekasi City in the industrial era 4.0.…”
Section: Introductionmentioning
confidence: 99%
“…According to several studies, virtual tours have not been found through digital showrooms for creative industry products that also allow for interaction between creative industry players and consumers. If this is successful, it will positively impact the development of Indonesia's creative industries (Rizkiyanti et al, 2021;Wahyudi et al, 2021;Zahro et al, 2019). Therefore, this service has been carried out in a virtual tourism-based digital batik village as a platform to promote batik in Bekasi City in the industrial era 4.0.…”
Section: Introductionmentioning
confidence: 99%